Temporal–Spatial Characterization of Seed Proteins and Oil in Widely Grown Soybean Cultivars across a Century of Breeding in China. Issue 2 (2nd February 2017) - Wu, Tingting; Yang, Xiushi; Sun, Shi; Wang, Caijie; Wang, Ying; Jia, Hongchang; Man, Weiqun; Fu, Lianshun; Song, Wenwen; Wu, Cunxiang; Yan, Hongrui; Jiang, Bingjun; et al.
Abstract : Soybeans [ Glycine max (L.) Merr.] are the predominant source of plant protein and vegetable oil in the human diet, and nutritional components, especially protein and oil, are important in soybean production and breeding. The current study aimed to identify the genetic progress of seed protein and oil in soybean cultivars grown widely over a century and to assess the spatial distribution of seed proteins and oil among four production regions (the Northern Heilongjiang region [NH], the Mid‐Southern Heilongjiang region [MSH], the Jilin and Liaoning region [JL], and the Huang‐Huai‐Hai River Valley [HH] region). Eighty‐nine widely grown soybean cultivars representing a span of 84 yr (1923–2007) of release were included, and a combination of analytical techniques was used to quantify seed protein, oil, amino acid, and fatty acid contents. It was found (i) that the temporal pattern over nine decades of genetic breeding exhibited a decreasing trend with regard to the concentrations of proteins and amino acids (arginine, glutamic acid, and histidine) and with stable trends for oil content. The fatty acid content showed variable changing patterns in different regions. (ii) The spatial distribution indicated the highest protein content and most fatty acids in the HH region and the lowest in the JL region; oil content showed the opposite pattern. (iii) Negative associations between protein and oil contents and yield were observed, with positive associations between protein content and contents of amino acids and most fatty acids. These results provide a comprehensive temporal–spatial profile of soybean seed proteins and oil in different regions and across different decades. These findings will help to provide strategies for manipulating the soybean composition and for improving soybean seed quality and nutritional value through genetic breeding.